The relationship between hindrance factors and working women's attitude towards pap smear screening test / Zuliana Azwa Zulkifli and Nur Hafizah Zainol Abidin - Zulkifli, Zuliana Azwa; Zainol Abidin, Nur Hafizah (2012)
Ministry of Health Malaysia in 2002, had ranked cervical cancer as second highest cancer cases reported in Malaysia. One way to detect cervical cancer is by using Pap Smear screening test. Despite of the importance of having Pap Smear screening test, the participation of women still in low level and becoming worse when the women is a career women. Among the reasons are low awareness, lack of spouse support and negative pre-assumption belief on the Pap Smear screening test cause women to hinder this test. Therefore this paper is aimed to determine the hindrance factors and the working women's attitude towards Pap Smear screening test in factory industry setting. Quantitative paradigm will be used where distribution of questionnaires is proposed as method of study. The data gained will be analyzed using SPSS version 16.0. The objective to identify the level of awareness and to analyze the relationship between hindrance factors and working women attitudes on Pap Smear screening test will be answered as according to previous findings.